Overexpression of Human-Derived DNMT3A Induced Intergenerational Inheritance of Active DNA Methylation Changes in Rat Sperm - Zheng, Xiaoguo; Li, Zhenhua; Wang, Guishuan; Li, Zhengzheng; Liang, Ajuan; Wang, Hanshu; Dai, Yubing; Huang, Xingxu; Chen, Xuejin; Ma, Yuanwu; Sun, Fei (Frontiers in Genetics, 2017)
DNA methylation is the major focus of studies on paternal epigenetic inheritance in mammals, but most previous studies about inheritable DNA methylation changes are passively induced by environmental factors. However, it is unclear whether the active changes mediated by variations in DNA methyltransferase activity are heritable. Here, we established human-derived DNMT3A (hDNMT3A) transgenic rats to study the effect of hDNMT3A overexpression on the DNA methylation pattern of rat sperm and to investigate whether this actively altered DNA methylation status is inheritable. Our results revealed that hDNMT3A was overexpressed in the testis of transgenic rats and induced genome-wide alterations in the DNA methylation pattern of rat sperm. Among 5438 reliable loci identified with 64 primer-pair combinations using a methylation-sensitive amplification polymorphism method, 28.01% showed altered amplified band types. Among these amplicons altered loci, 68.42% showed an altered DNA methylation status in the offspring of transgenic rats compared with wild-type rats. Further analysis based on loci which had identical DNA methylation status in all three biological replicates revealed that overexpression of hDNMT3A in paternal testis induced hypermethylation in sperm of both genotype-negative and genotype-positive offspring. Among the differentially methylated loci, 34.26% occurred in both positive and negative offspring of transgenic rats, indicating intergenerational inheritance of active DNA methylation changes in the absence of hDNM3A transmission. Furthermore, 75.07% of the inheritable loci were hyper-methylated while the remaining were hypomethylated. Distribution analysis revealed that the DNA methylation variations mainly occurred in introns and intergenic regions. Functional analysis revealed that genes related to differentially methylated loci were involved in a wide range of functions. Finally, this study demonstrated that active DNA methylation changes induced by hDNMT3A expression were intergenerationally inherited by offspring without transmission of the transgene, which provided evidence for the transmission of active endogenous-factors-induced epigenetic variations.